Respuesta :

Answer:

Step-by-step explanation:

Expression on the board :

[tex]12.2x + 50.6 y + 3(1.4x - 2.6y)\\\\= 12.2x + 50.6y + 4.2x - 7.8y\\\\= 16.4x + 42.8y[/tex]

Expression by the student :

Expression 1 :

[tex]4 ( 4.1x + 10.7 y ) \\\\= ( 4 \times 4.1x ) + ( 4 \times 10.7 y)\\\\= 16.4x + 42.8y\\\\[/tex]

The expression 1 is equivalent to the expression on the board. Because the coefficients of x and y are same on both.

Expression 2 :

[tex]2 ( 6.1x + 25.3 y + 2.1x -3.9y)\\\\= 2 ( 8.2x + 21.4y)\\\\=( 2 \times 8.2x ) + (2 \times 21.4y)\\\\= 16.4x + 42.8y[/tex]

The expression 2 is also equivalent to the expression on the board. Because the coefficients of x and y are the same.

ACCESS MORE